2018
DOI: 10.21067/jpm.v3i2.2702
|View full text |Cite
|
Sign up to set email alerts
|

Sosialisasi Kekompakan Tim Melalui Outbound pada Kelompok Sadar Wisata Desa Mojo Kabupaten Bojonegoro

Abstract: The socialization program for team cohesiveness was carried out at the Tourism Awareness Group (Pokdarwis) of Mojo Village. This Pokdarwis has just been formed and has a role in managing boat tours and star fruit plantation tourism owned by Mojo Village. Boat tours and star fruit gardens are the mainstay of Mojo Village. The socialization for team cohesiveness was carried out with 33 people targeting the entire Pokdarwis group. Outbound activities are carried out indoors and outdoors for one full day. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Banyak memiliki potensi buah tropis, menjadikan Kecamatan Kalitidu memiliki banyak desa dengan potensi Agrowisata, seperti Desa Mojo. Tanah perkebunan belimbing yang dimiliki sebesar 15,5 ha dengan hasil panen mencapai 424,7 ton/th (Andajani, Widjaja, and Prihatiningrum 2017). Melihat hal tersebut, masyarakat Desa Mojo melihat peluang untuk membuka usaha, seperti Agrowisata dan hasil olahan belimbing.…”
Section: Pendahuluanunclassified
“…Banyak memiliki potensi buah tropis, menjadikan Kecamatan Kalitidu memiliki banyak desa dengan potensi Agrowisata, seperti Desa Mojo. Tanah perkebunan belimbing yang dimiliki sebesar 15,5 ha dengan hasil panen mencapai 424,7 ton/th (Andajani, Widjaja, and Prihatiningrum 2017). Melihat hal tersebut, masyarakat Desa Mojo melihat peluang untuk membuka usaha, seperti Agrowisata dan hasil olahan belimbing.…”
Section: Pendahuluanunclassified
“…On the other hand, Astawa et al (2019) showed that the Tourism Awareness Group (Pokdarwis) could pioneer ecological-based development. Therefore, various training to increase the capacity of Human Resources (HR) are needed to support the activities of the Tourism Awareness Group (Pokdarwis) in optimizing tourist destinations (Andajani et al, 2018;Anggraini, 2012;Sudipa et al, 2010Sudipa et al, , 2012Widodo, 2019).…”
Section: Sitalang Tourism Awareness Group and The Form Of Social Capitalmentioning
confidence: 99%
“…Outbound merupakan metode pelatihan untuk pengembangan diri (personal development) dan tim (team development) dalam proses mencari pengalaman melalui kegiatan di alam terbuka (Agusta, Setyosari, & Sa'dijah, 2018). Outbound tidak hanya dapat dilakukan oleh orang dewasa atau hanya di dalam dunia pekerjaan, tetapi di Indonesia sekarang outbound sudah lebih dikembangkan lagi dengan pembelajaran untuk anak-anak yang masih belia (Andajani, Rahayu, & Prihatiningrum, 2018;Yunaida & Rosita, 2018).…”
Section: Gambar 2 Diagram Klasifikasi Tingkat Kesegaran Jasmani Siswaunclassified